2x-(-7)=3(x+10)

Simple and best practice solution for 2x-(-7)=3(x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(-7)=3(x+10) equation:


Simplifying
2x + -1(-7) = 3(x + 10)

Multiply -1 * -7
2x + 7 = 3(x + 10)

Reorder the terms:
7 + 2x = 3(x + 10)

Reorder the terms:
7 + 2x = 3(10 + x)
7 + 2x = (10 * 3 + x * 3)
7 + 2x = (30 + 3x)

Solving
7 + 2x = 30 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
7 + 2x + -3x = 30 + 3x + -3x

Combine like terms: 2x + -3x = -1x
7 + -1x = 30 + 3x + -3x

Combine like terms: 3x + -3x = 0
7 + -1x = 30 + 0
7 + -1x = 30

Add '-7' to each side of the equation.
7 + -7 + -1x = 30 + -7

Combine like terms: 7 + -7 = 0
0 + -1x = 30 + -7
-1x = 30 + -7

Combine like terms: 30 + -7 = 23
-1x = 23

Divide each side by '-1'.
x = -23

Simplifying
x = -23

See similar equations:

| 24x^2+47x+k=0 | | (3m+8)(5m-3)= | | -8.6-3z-8.5-z=-3z+2.3 | | 2(1-x)=3(x+9) | | n+12=n*4 | | 2y+3=7y | | 5(x-7)=2(x+8)+x | | 12-2x+5=-2+(x-3) | | 4(3x-5)-x=-x+16 | | -3m+7=40 | | 3x-2=3x-5+8 | | 4w+6w= | | 3(2x-1)+x=x-3 | | x-10-2x=9 | | 0=x^2-10x+50 | | 5x+5(1-x)=x+8 | | 9x-(4x-3)=11+(2x-2) | | 2x-12=3x-16 | | -3x^3-7x^2-5x+1= | | 19(13a+20)= | | 3x^3-7x^2-5x+1= | | n^2+6n-86=5 | | 12x+3=1232342 | | u^2-8u+16=0 | | 33=-8+4(c-5) | | 35x^3-28x^2=7x | | 4x^2+48=0 | | 5y=8-9y | | 21=-9(8r-3) | | 20x^2-20x^2= | | 4z-9z=6z-3+2 | | 2x+4=2x+16 |

Equations solver categories